Experimental assessment of systemic toxicity of implants on magnesium alloy base - Golovakha, Maksim; Belyenichev, Igor; Zhernovaya, Galina; Chorny, Vadim; Yatsun, Yevgeniy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
On the basis of previous studies we have proposed a new material, which is produced by alloying with silver of industrial magnesium alloy ML-10. But question about impact of products of the resolution of magnesium alloy on organism has not been fully elucidated. Objective: to evaluate experimentally general toxic effect of magnesium-based alloy implants on rats. Materials: Material of this study wrer experimental animals (n = 14) with above mentioned implants injected into the thigh muscles and intact (n = 6) rats. We investigated the performance of protein and nitrite in urine as well as behavioral responses. Results: The results of the study of the dynamics of change in body weight of animals showed no signs of intoxication, and during the regular studies of the scalp and mucous membranes any abnormalities were not detected. In assembled urine of animals with help of the metabolic chamber there were found only traces of protein. There was not found any significant differences of nitrite content in daily urine in intact and experimental groups in terms of monitoring. Evaluation of the tentative research behavior in the «open field» showed that on the 2nd day after surgery the overall rate of locomotor activity and research behavior in rats with implants decreased on 60.6 % which may be explained by surgical trauma. Subsequently, indicators of locomotor activity in experimental and intact groups did not differ significantly which is important in terms from 2 to 6 months after surgery when one may expect maximum toxic effect from biodegradation of alloy. Conclusions: These results show an absence of toxic effects of products of biodegradation of magnesium-based alloy. They may serve as experimental rationale for clinical testing of implants made of this alloy.